An examination of correlates of simultaneous opioid and benzodiazepine use among patients in medication treatment for opioid use disorder in a small midwestern community. Issue 4 (3rd October 2022) - Ellis, Jennifer D.; Pasman, Emily; Brown, Suzanne; Lister, Jamey J.; Agius, Elizabeth; Resko, Stella M.
Abstract: Background: Concurrent and/or simultaneous use of opioids and benzodiazepines has been associated with increased risk of accident and injury, as well as with co-occurring psychopathology. Objectives: The purpose of the present study was to explore potential correlates of simultaneous opioid and benzodiazepine use in a small community, including perceived risk, positive screens for psychiatric symptoms, and opioid-related consequences. Methods: A sample of 267 participants were recruited from a medication treatment provider that serves a small Midwestern community. Multinomial logistic regression was used to explore demographic and mental health correlates associated with self-reports of past-year simultaneous use. Zero-inflated Poisson regression was used to explore past-year consequences associated with reported simultaneous benzodiazepine and opioid use. Results: Intentional simultaneous use of opioids and benzodiazepines was associated with greater anxiety and depression symptoms, greater likelihood of a positive PTSD screen, and low self-perceived risk of simultaneous use. Individuals reporting opioid/benzodiazepine simultaneous use were also more likely to report opioid-related consequences. Conclusions: Results highlight the importance of assessing and treating simultaneous opioid/benzodiazepine co-use, as well as relevant comorbidities.